Continuation or Discontinuation of Anticoagulation in the Early Phase After Acute Ischemic Stroke. Issue 7 (July 2018) - Groot, Adrien E.; Vermeij, Jan-Dirk M.; Westendorp, Willeke F.; Nederkoorn, Paul J.; van de Beek, Diederik; Coutinho, Jonathan M.
Abstract : Background and Purpose—: There is no consensus on whether anticoagulation should be continued or temporarily stopped in patients suffering acute ischemic stroke while using anticoagulation. We assessed treatment variations and outcomes in these patients. Methods—: Post hoc analysis of PASS (Preventive Antibiotics in Stroke Study). We included patients with acute ischemic stroke who used anticoagulation at admission. We compared clinical outcomes, thrombotic, and major bleeding events at 3 months. Results—: Nine percent (192/2101) of the patients with acute ischemic stroke used anticoagulation at admission (186 vitamin K antagonists). Anticoagulation was discontinued in 35/192 (18%) patients. These patients had higher National Institutes of Health Stroke Scale scores than patients in whom anticoagulation was continued (median, 13 versus 4; P <0.001). Thrombotic events occurred more frequently in patients in whom anticoagulation was discontinued (11% versus 3%; P =0.038). There were no major bleeding events in either group. Mortality and clinical outcomes at 90 days were worse in patients in whom anticoagulation was discontinued (mortality, 31% versus 15%; P =0.019 and modified Rankin Scale score of 0–2, 20% versus 55%; P <0.001). After adjustment for potential confounders, there were no statistically significant differences between groups. Conclusions—: In our study, clinicians tended to continue anticoagulation in patients with acute ischemic stroke. Discontinuation was associated with an increased risk of thrombotic events and worse clinical outcome. Risk of major bleeding was not increased in patients in whom anticoagulation was continued. Clinical Trial Registration—: URL: https://www.controlled-trials.com . Unique identifier: ISRCTN66140176. Abstract : Supplemental Digital Content is available in the text.